2018
DOI: 10.1080/0284186x.2018.1478125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental socioeconomic factors on childhood cancer mortality: a population-based registry study

Abstract: Despite high quality public health care and comprehensive social security, both high parental income and education were associated with lower mortality after childhood cancer. Lower health literacy and financial pressures limiting treatment adherence may explain higher mortality in children with less educated parents and parents with lower income. Motivation and support during treatment and follow-up period is needed concerning the families of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 16 publications
3
46
1
Order By: Relevance
“…In this nationwide population‐based study, the aim was to investigate the effect of immigrant status of the patient and the parents on childhood cancer mortality and survival. In our previous study, we found that low socioeconomic status of the parents was a predictor for higher mortality among childhood cancer patients . Thus, we hypothesize that similar inequalities may be found based on immigrant status as well.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…In this nationwide population‐based study, the aim was to investigate the effect of immigrant status of the patient and the parents on childhood cancer mortality and survival. In our previous study, we found that low socioeconomic status of the parents was a predictor for higher mortality among childhood cancer patients . Thus, we hypothesize that similar inequalities may be found based on immigrant status as well.…”
Section: Introductionmentioning
confidence: 59%
“…In our previous study, we found that low socioeconomic status of the parents was a predictor for higher mortality among childhood cancer patients. 14 Thus, we hypothesize that similar inequalities may be found based on immigrant status as well. The strength of our study lies in having accurate information on origin of birth and the coverage of the entire immigrant population in Finland based on national registries.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, health care professionals may behave differently towards those in a lower socioeconomic status than towards those in a higher status, therefore hindering participation in decision‐making and engagement in the treatment process (30). It may be that endodontic treatment quality is less prone to the common deficiencies of patient‐professional engagement than longer and more socially complex treatments related to, for example, cancer (31) or human immunodeficiency virus (HIV) (32), for which considerable socioeconomic differences favouring the socioeconomically better‐off have been shown.…”
Section: Discussionmentioning
confidence: 99%